2020
DOI: 10.1021/acs.oprd.0c00217
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Scalable Synthesis and Process for EMA401, Part III: Using an Engineered Phenylalanine Ammonia Lyase Enzyme to Synthesize a Non-natural Phenylalanine Derivative

Abstract: A process using an engineered phenylalanine ammonia lyase (PAL) enzyme was developed as part of an alternative route to a key intermediate of olodanrigan (EMA401). In the first part of this report, the detailed results from a screening for the optimal reaction conditions are presented, followed by a discussion of several workup strategies investigated. In the PAL-catalyzed reaction, 70−80% conversion of a cinnamic acid derivative to the corresponding phenylalanine derivative could be achieved. The phenylalanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“… 26 Despite the increased attention for the industrial applicability of PAL-based procedures, no other studies reported immobilized PAL preparations with high operational stability in ammonia addition, while an attempt described within the PAL process development for EMA401 (ref. 7 ) has supported the existence of such interests. Accordingly, using SWCNT-based supports, the best performing in our previous studies, a site-oriented immobilization procedure was established using a maleimide moiety containing linker that was attached directly to amino-functionalized carbon nanotubes (SWCNT NH 2 ) or to carboxy-functionalized carbon nanotubes (SWCNT COOH ), priorly activated with carbonyldiimidazole and functionalized with 1,3-diaminopropane ( Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“… 26 Despite the increased attention for the industrial applicability of PAL-based procedures, no other studies reported immobilized PAL preparations with high operational stability in ammonia addition, while an attempt described within the PAL process development for EMA401 (ref. 7 ) has supported the existence of such interests. Accordingly, using SWCNT-based supports, the best performing in our previous studies, a site-oriented immobilization procedure was established using a maleimide moiety containing linker that was attached directly to amino-functionalized carbon nanotubes (SWCNT NH 2 ) or to carboxy-functionalized carbon nanotubes (SWCNT COOH ), priorly activated with carbonyldiimidazole and functionalized with 1,3-diaminopropane ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“… 4 The PAL-based ammonia addition reaction of cinnamic acid derivatives has multiple advantages over other synthetic methods, such as a 100% atom economy, high enantioselectivity, low-cost, easily accessible substrates, and no requirement for a cofactor or its regeneration. 4,5 PALs are already used in established industrial processes, such as the multi-ton scale production of ( S )-2,3-dihydro-1 H -indole-2-carboxylic acid by DSM 6 or of (3 S )-5-(benzyloxy)-2-(diphenylacetyl)-6-methoxy-1,2,3,4-tetrahydroisoquinoline-3-carboxylate (EMA401) by Novartis 7 ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of such reagents was however historically limited by the biotransformations achieved by natural enzymes, and by their substrate specificity. Recently, the engineering of novel enzymes optimized for specific reactions [10] enabled the extension of their application range, including unconventional biotransformations such as stereo-controlled halogenations [11] (Fig. 2).…”
Section: The Potential Of Biotransformationsmentioning
confidence: 99%
“…Out of the routes described in this publication, the asymmetric hydrogenation as published by Burk et al was the preferred option for early phase deliveries, while the biocatalytic approach using phenylalanine ammonia lyase (PAL) described in part III of this series of manuscripts would have been the preferred option for late phase clinical trials. 21 For the theoretical impurity BCME, potentially formed in the penultimate bond forming step, we analyzed its formation based on literature and compared the results from spiking experiments with the purge factor obtained by applying ICH M7 control option 4. Our results for both strategies showed that BCME was purged below levels of toxicological concern in the drug substance.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…These findings are disclosed in parts II and III of this publication series. 20,21 Investigations on the Theoretical Impurity Bis-(chloromethyl) ether. Bis(chloromethyl) ether (BCME; CAS #542-888-1) is a highly toxic compound and known mutagen, classified as an ICH M7 class 1 impurity.…”
Section: ■ Introductionmentioning
confidence: 98%